2007
DOI: 10.1242/jcs.002949
|View full text |Cite
|
Sign up to set email alerts
|

BMP-9 signals via ALK1 and inhibits bFGF-induced endothelial cell proliferation and VEGF-stimulated angiogenesis

Abstract: Genetic studies in mice and humans have shown that the transforming growth factor-β (TGF-β) type-I receptor activin receptor-like kinase 1 (ALK1) and its co-receptor endoglin play an important role in vascular development and angiogenesis. Here, we demonstrate that ALK1 is a signalling receptor for bone morphogenetic protein-9 (BMP-9) in endothelial cells (ECs). BMP-9 bound with high affinity to ALK1 and endoglin, and weakly to the type-I receptor ALK2 and to the BMP type-II receptor (BMPR-II) and activin type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
498
6
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(532 citation statements)
references
References 49 publications
23
498
6
5
Order By: Relevance
“…In addition, endoglin has been shown to interact with zyxin-related protein 1 resulting in a dramatic change in the structure of the actin cytoskeleton and the localization of zyxinrelated protein 1 (Sanz-Rodriguez et al, 2004). Second, in addition to TGF-b1, endoglin can bind, in association with different TGF-b superfamily receptors, to BMP2, BMP7, BMP9, activin A and TGF-b3 (Cheifetz et al, 1992;Barbara et al, 1999;Scharpfenecker et al, 2007), and has been reported to have a functional role in modulating responses to BMP2 (Ishibashi et al, 2010) and BMP7 (Scherner et al, 2007) in periodontal ligament cells and myoblasts, respectively. Although there are no published reports of endoglin modulating the response to other TGF-b family ligands in epithelial cells, it will be of interest in the future to determine whether the TGF-b1-independent functions of endoglin expressed on tumor cells may be mediated by binding to alternate ligands and/ or other TGF-b superfamily receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, endoglin has been shown to interact with zyxin-related protein 1 resulting in a dramatic change in the structure of the actin cytoskeleton and the localization of zyxinrelated protein 1 (Sanz-Rodriguez et al, 2004). Second, in addition to TGF-b1, endoglin can bind, in association with different TGF-b superfamily receptors, to BMP2, BMP7, BMP9, activin A and TGF-b3 (Cheifetz et al, 1992;Barbara et al, 1999;Scharpfenecker et al, 2007), and has been reported to have a functional role in modulating responses to BMP2 (Ishibashi et al, 2010) and BMP7 (Scherner et al, 2007) in periodontal ligament cells and myoblasts, respectively. Although there are no published reports of endoglin modulating the response to other TGF-b family ligands in epithelial cells, it will be of interest in the future to determine whether the TGF-b1-independent functions of endoglin expressed on tumor cells may be mediated by binding to alternate ligands and/ or other TGF-b superfamily receptors.…”
Section: Discussionmentioning
confidence: 99%
“…While BMP-9-induced heterotopic ossification was shown to be mediated through the ALK1 type 1 receptor, the study does not address whether ALK1 acts independently of other BMP type 1 receptors or other receptors contribute to heterotopic ossification, perhaps through type 1 BMP receptor heterodimer formation with ALK1. Although experimental data support that ALK1 binds BMP-9 and activates the BMP-Smad1/5/ 8 pathway in response to BMP-9, (11) there is additional evidence that BMP-9 binds to and signals through receptors other than ALK1, including ALK2, (12,13) the BMP type 1 receptor that is mutated in patients with FOP. (4) It is interesting to speculate that in these experiments, BMP-9 in the context of injury is inducing heterotopic ossification by activating ALK1-ALK2 heterodimers or that a sequential series of BMP signaling events mediated independently by ALK1 and ALK2 is required for induction of heterotopic ossification.…”
mentioning
confidence: 99%
“…Ce modèle est actuellement remis en cause car en 2006, notre groupe a identifié les facteurs BMP9 et BMP10 comme des ligands spécifiques et de forte affinité d'ALK1 [24]. Ces résultats ont été confirmés depuis par un autre groupe [25]. L'expression de BMP10 semble restreinte au stade embryonnaire et jouerait un rôle dans le développement du coeur.…”
Section: Identification Des Ligands Du Récepteur Alk1 : Bmp9 Et Bmp10unclassified
“…Le rôle du récepteur ALK1, en l'absence de ligand spécifique, a longtemps été débattu dans la littérature [27,28]. L'identification de son ligand BMP9 a permis de confirmer clairement son rôle dans l'inhibition de la prolifération, de la migration et du bourgeonnement des cellules endothéliales in vitro ainsi que de la néo-angiogenèse in vivo [24][25][26]. Ces données indiquent que BMP9 serait un facteur-clé de la phase de maturation de l'angiogenèse ( Figure 1) et sa présence dans le sang suggère son rôle dans le maintien de la quiescence vasculaire chez l'adulte [26].…”
Section: Identification Des Ligands Du Récepteur Alk1 : Bmp9 Et Bmp10unclassified